Manpower Establishment resource plan result and setup presentation - Shirzad, Azadeh (My University, 2009)
The aim of this master thesis was to analyze the current presentation of data in the crew planning system for airlines and to give suggestions for changes and/or present new ways of representing data either in figure or in graphics. The main demand was to provide users with essential information in a comprehensible and an easy-to-use way. This thesis was a way to enlighten the existing problems in the system and to show how these problems can be solved by considering the users’ needs while keeping Interaction Design principles in mind. In order to analyze the existing problems and to achieve the thesis goal different methods such as Documentation analysis, Interview, Cognitive Walkthrough, Morphological charts and Iterative Design and Prototyping were used. Jeppesen develops software for airlines, ships and trains. Manpower is one of the new software which is developed by Jeppesen for managing airline crew and one of their first clients is SAS. SAS is now in production phase meaning that they are testing the system and are using it in parallel with the old system that they got. This gives them the opportunity to both get acquainted with the system and debug Manpower. Because of SAS being in acceptance phase and end-users not being located in Gothenburg, unfortunately only one visit has been paid to end-users. Most of the information has been provided by internal users at Jeppesen. After gathering the information and analyzing the results of interviews, paper prototyping was done and internal users were asked to evaluate the prototypes. In two rounds of iteration, users’ suggestions were considered and the final decision was made. For the reason that all the suggestions could not be implemented in the time format of the thesis, users were asked to vote for the three most important features which needed to be implemented. The result was reviewed and the one which fitted in the time frame was picked to be programmed. I am proud to say this work had a fruitful result and most of the design ideas were cherished by Jeppesen.
Keywords: Datalogi; Bildanalys; Övrig informationsteknik; Computer science; Image analysis; Other information technology